2005
DOI: 10.1021/bi048135v
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Stability of Carbonic Anhydrase:  Measurements of Binding Affinity and Stoichiometry Using ThermoFluor

Abstract: ThermoFluor (a miniaturized high-throughput protein stability assay) was used to analyze the linkage between protein thermal stability and ligand binding. Equilibrium binding ligands increase protein thermal stability by an amount proportional to the concentration and affinity of the ligand. Binding constants (K b ) were measured by examining the systematic effect of ligand concentration on protein stability. The precise ligand effects depend on the thermodynamics of protein stability: in particular, the unfol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
488
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 452 publications
(520 citation statements)
references
References 23 publications
(42 reference statements)
28
488
0
4
Order By: Relevance
“…This biophysical technique can be applied to any protein-ligand non-covalent binding reaction, independent of whether the ligand stabilizes or destabilizes the protein upon binding 25 . In cases when there is a single binding event, the ITC and TSA results complement each other for increased precision of the measurements 26 . In addition, the method is useful for the…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…This biophysical technique can be applied to any protein-ligand non-covalent binding reaction, independent of whether the ligand stabilizes or destabilizes the protein upon binding 25 . In cases when there is a single binding event, the ITC and TSA results complement each other for increased precision of the measurements 26 . In addition, the method is useful for the…”
Section: Introductionmentioning
confidence: 91%
“…A 10% uncertainty in the value of unfolding enthalpy yields an uncertainty of the binding constant of ~2 fold 26 . The enthalpy of unfolding can be determined using several biophysical techniques such as DSC and acid-titration ITC 47; 48 , and by fitting raw TSA curves or ligand-dosing curves 40 .…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…We have previously established a microplatebased technique for measuring protein stability to denaturants, the effects of mutations, complex denaturation pathways, and ligand affinities, based on the classical measurement of intrinsic protein fluorescence, 6,7 removing the need for extrinsic fluorophores such as 1-anilino-8-naphthalene-sulfonate (ANS) used in earlier experiments at the microplate scale, 8 but which can alter the solubility and stability of proteins and also their interactions with other molecules. While this technique improved throughput considerably over autotitration methods in fluorometers, 9 there is a further need for increased throughput and decreased sample volume to match the increasing size and small-scale syntheses of combinatorial compound libraries in drug discovery, 10 for the evolutionary engineering of proteins, 11 and for protein bioprocess formulation.…”
Section: Introductionmentioning
confidence: 99%
“…This network stabilized a particular active site conformation that the authors suggested promoted greater global stability. [7] Here we probe the effects of IFG-binding in solution on GCase global stability by differential scanning fluorimetry [18][19][20][21][22] and on local dynamics by amide hydrogen/ deuterium exchange coupled with proteolysis and mass spectrometry (H/D-Ex). [23][24][25][26][27][28] The ability to partially restore intracellular trafficking and lysosomal GCase localization of mutant forms of GCase was then inferred from activity assays performed on N370S/N370S and F213I/L444P patient fibro-blasts.…”
mentioning
confidence: 99%